Implementasi Pengaturan Adaptasi Perubahan Iklim di Sektor Pertanian dalam Mencapai Ketahanan Pangan di Indonesia - Abdullah Azzam Alhudhaibi; Ida Nurlinda; Nadia Astriani (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
The negative impacts of the climate change phenomenon have a very broad impact, including on the agricultural sector, thus threatening food resilience in Indonesia. This research aims to find out how the regulation of climate change adaptation in the agricultural sector achieves food resilience in Indonesia, and to find out how its implementation occurs specifically in the regency of Kubu Raya, West Kalimantan Province, and Bandung City, West Java Province. Using a normative legal and analytical-descriptive approach, the main data are primary legal data and legal literature. The results showed that there are several climate change adaptation provisions in the agricultural sector in Indonesia, but food diversification as an adaptation measure is not contained in them. This makes the implementation of the agreements in Kubu Raya constituency try to adapt only to a commodity. Nevertheless, the implementation of climate change adaptation in the agricultural sector, especially in Kubu Raya constituency and Bandung city, has been pursued despite the respective problems outside the threat of climate change.